2014
DOI: 10.1021/ja5086996
|View full text |Cite
|
Sign up to set email alerts
|

Bipyrrole-Strapped Calix[4]pyrroles: Strong Anion Receptors That Extract the Sulfate Anion

Abstract: Cage-type calix[4]pyrroles 2 and 3 bearing two additional pyrrole groups on the strap have been synthesized. Compared with the parent calix[4]pyrrole (1), they were found to exhibit remarkably enhanced affinities for anions, including the sulfate anion (TBA(+) salts), in organic media (CD2Cl2). This increase is ascribed to participation of the bipyrrole units in anion binding. Receptors 2 and 3 extract the hydrophilic sulfate anion (as the methyltrialkyl(C(8-10))ammonium (A336(+)) salt) from aqueous media into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 21 publications
1
56
1
Order By: Relevance
“…Anions are known to bind to the central protons of expanded free-base porphyrins and related macrocyclesi nt heir neutral form, [40][41][42][43][44][45][46][47] and one of our interests in the present study was to investigate how changes in the supporting electrolyte anion would affect both the measured reduction potentials and the stabilityo ft he porphyrin products formed in the first and/or second reduction on the electrochemical and spectroelectrochemical timescale. Examples of the electrochemical data are given in Figures S3 and S4, which illustrate cyclic voltammograms of H 2 TPP in the four solvents containing TBAX, where X = Cl À ,Br À ,I À ,and ClO 4 À .…”
Section: Effectsofs Olvent and Supporting Electrolyte On The Reductiomentioning
confidence: 99%
“…Anions are known to bind to the central protons of expanded free-base porphyrins and related macrocyclesi nt heir neutral form, [40][41][42][43][44][45][46][47] and one of our interests in the present study was to investigate how changes in the supporting electrolyte anion would affect both the measured reduction potentials and the stabilityo ft he porphyrin products formed in the first and/or second reduction on the electrochemical and spectroelectrochemical timescale. Examples of the electrochemical data are given in Figures S3 and S4, which illustrate cyclic voltammograms of H 2 TPP in the four solvents containing TBAX, where X = Cl À ,Br À ,I À ,and ClO 4 À .…”
Section: Effectsofs Olvent and Supporting Electrolyte On The Reductiomentioning
confidence: 99%
“…11 While a number of receptors for selective sulfate recognition have recently been reported, [13][14][15][16][17][18][19][20][21][22][23][24][25] there are relatively few examples of suitable receptors that overcome the Hofmeister bias to allow LLE of sulfate. [26][27][28][29][30][31][32][33] Sessler and co-workers have successfully employed calix[n]pyrroles to extract sulfate into organic media in the presence of methyltrialkylammonium ions. [26][27][28] Wu and co-workers have demonstrated that a tripodal hexaurea receptor is capable of extraction of sulfate ions into chloroform solution in the presence of TBACl and that the sulfate can be back-extracted with aqueous barium chloride to regenerate the receptor as a chloride complex.…”
Section: Introductionmentioning
confidence: 99%
“…Such high fluoride anion selectivity can be attributed to the presence of the bulky calix [4]arene cap, which possesses phenyl spacers that are less flexible and thus increase the rigidity of the calix [4]pyrrole core. [57] Copyright (2014) American Chemical Society. 1 H NMR titration in CDCl 3 has also revealed that receptor 9 binds fluoride anions in its monohydrated form.…”
Section: -mentioning
confidence: 99%